Modelling of River Flows, Sediment and Contaminants Transport - Krishnappan, Bommanna (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book presents five articles that are also part of a Special Issue titled: Modelling of River flows, Sediment and Contaminants Transport published in the Water Journal under the section: Water Erosion and Sediment Transport. It covers a wide range of topics, such as predicting the impacts of wildfires on sediment transport and water quality in a mountainous region and estimating the sediment erosion due to release of ice-jams in cold region rivers.